2009
DOI: 10.1111/j.1365-2923.2008.03270.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming an academic doctor: perceptions of scholarly careers

Abstract: Results suggest that opportunities should be structured within undergraduate and graduate medical education to stimulate interest in careers as academic doctors and to aid junior faculty members to act as role models who can encourage learners to pursue careers in academic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…In some highly successful academic centers, offering a 1-year research experience resulted in a 10% increase in the number of students who reported an interest in pursuing a research-related career 41 , consistent with other reports suggesting that an intensive research experience influences the intentions to pursue academic careers 38,39,58,59 . The actual career choice and the long-term impact of research experiences on student's careers (academic or nonacademic) and on their professional performance is difficult to assess.…”
supporting
confidence: 73%
“…In some highly successful academic centers, offering a 1-year research experience resulted in a 10% increase in the number of students who reported an interest in pursuing a research-related career 41 , consistent with other reports suggesting that an intensive research experience influences the intentions to pursue academic careers 38,39,58,59 . The actual career choice and the long-term impact of research experiences on student's careers (academic or nonacademic) and on their professional performance is difficult to assess.…”
supporting
confidence: 73%
“…These findings are similar to other studies that examined the role of these factors in student planning of academic careers. 12,20,25,[29][30][31] In our model, international medical graduate status did not significantly influence residents' subspecialty career goal.…”
Section: Discussionmentioning
confidence: 83%
“…This lack of skills may arise from inadequate early exposure to the basic concepts of scientific inquiry that serves to limit their later research involvement [4951]. While in some countries students had research exposure before medical school, they still did not feel prepared enough to engage in research [35,47,50]. A plausible explanation could be that the previous research experience was not targeted enough to facilitate their participation in applied research during medical school.…”
Section: Discussionmentioning
confidence: 99%